THE EFFECT OF INDEPENDENT LEARNING ON CRITICAL THINKING SKILLS MEDIATED BY LEARNING MOTIVATION IN ONLINE LEARNING DURING A PANDEMIC - Wahyuningsih, Putri; Usman, Osly; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This research aims to determine the effect of independent learning on critical thinking skills mediated by learning motivation in students of the Faculty of Social Sciences, State University of Jakarta 2018. This study uses a descriptive quantitative approach with a survey method. The population in this study amounted to 767 students and the sample in this study was 332 students. The respondent selection technique used proportional random sampling, namely using the proportional random method. In data management, the researcher processed the questionnaire using a Likert scale. The variables of Critical Thinking Ability, Learning Independence, and Learning Motivation are data. The results showed that learning independence had an effect on critical thinking skills with learning motivation as a mediation between the two.